The Simulation of the Behavior of a Student-Created Operating System using GPSS - Droucas, George (My University, 1976)
While operating system concepts are taught to students in undergraduate programs in Computer Science, a student project involving the development of an operating system creates a difficult situation due to time and financial considerations. Using GPSS to simulate the behavior of a student-treated operating system can reduce these problems and serve as an effective learning device. Many features and concepts can be simulated that might otherwise be ignored in a student project. An implementation of a student-created operating system is discussed. Statistics collected from the GPSS simulated model are used to operating system.
Keywords: Computer Engineering; Computer Engineering